The Effect of Sales Growth and Firm Size on Profitability in Healthcare Companies Listed on the Indonesia Stock Exchange - Astri Amanda Nur Aeny; Fitri Rahmiyatun; Sugiarti Sugiarti; Hartanti Hartanti (SEAN Institute, 2026)
This study aims to analyze the effect of Sales Growth and Firm Size on profitability in healthcare companies listed on the Indonesia Stock Exchange during the 2021–2023 period. Profitability was measured using Return on Assets (ROA), while Sales Growth and Firm Size were used as independent variables. This research employed a quantitative approach using secondary data obtained from annual financial reports of healthcare companies listed on the Indonesia Stock Exchange. The sampling technique used was purposive sampling, resulting in sixteen companies selected as research samples. Data analysis was conducted using multiple linear regression analysis with SPSS version 26. The results indicate that Sales Growth does not have a significant effect on profitability, while Firm Size has a significant negative effect on profitability. Simultaneously, Sales Growth and Firm Size significantly affect profitability. These findings suggest that increasing company size may create operational inefficiencies that reduce profitability, while sales growth alone is insufficient to improve financial performance without effective operational and cost management.